Investigating the Mechanism of Rhizoma Coptidis-Eupatorium fortunei Medicine in the Treatment of Type 2 Diabetes Based on Network Pharmacology and Molecular Docking. - Li, Huan; Luo, Dan; Wei, Ran; Sun, Mingliang; Zhang, Xi; Deng, Huan; Bian, Wenfei; Wei, Haoyue; Huang, Yanqin (BioMed Research International, 2022)
Objective. This study systematically explored the mechanism of Rhizoma Coptidis-Eupatorium fortunei in treating type 2 diabetes mellitus (T2DM) by using network pharmacology and molecular docking methods. Methods. The TCMSP database was used to screen out the active ingredients and related targets of Rhizoma Coptidis-Eupatorium fortunei (R-E) drug pair. GeneCards, OMIM, DrugBank, and other databases were used to screen the related targets of T2DM, and then, the UniProt database was used to standardize the relevant targets of T2DM. Then, the Venn analysis was performed on the active ingredient-related targets and disease-related targets of R-E drugs to find the intersection targets. Using the STRING database and Cytoscape software, the PPI network and "drug-active ingredient-target-disease" network are constructed by intersecting targets and corresponding active ingredients. Through the cluster profiler package in the R software, GO function enrichment analysis and KEGG pathway enrichment analysis were carried out on the intersection targets and the screened core targets, and the prediction results were verified by molecular docking. Results. Taking OB ≥ 30 % and DL ≥ 0.18 as the standard, a total of 25 effective active ingredients of R-E drug pairs were screened, including berberine, palmatine, coptisine, and so on. After corresponding, 19 effective chemical components and 284 targets of the R-E drug pair were obtained. After searching multiple disease databases, 1289 T2DM-related targets were screened. After the summary, 159 common targets were obtained in this study. Finally, in the bioinformatics analysis, this study concluded that quercetin, luteolin, berberine, palmatine, and coptisine are the main chemical components of the R-E drug pair. ESR1, MAPK1, AKT1, TP53, IL6, and JUN are the important core targets. GO and KEGG enrichment analyses showed that Rhizoma Coptidis-Eupatorium fortunei could improve T2DM by regulating multiple biological processes and pathways. Molecular docking results showed that berberine, palmatine, and coptisine had higher binding to the core target, and MAPK1, AKT1, and IL6 could stably bind to the active ingredients of Rhizoma Coptidis-Eupatorium fortunei. Conclusion. Rhizoma Coptidis-Eupatorium fortunei may have therapeutic effects on T2DM such as anti-inflammatory and regulating glucose and lipid metabolism through multiple components, multiple targets, and multiple signaling pathways, which provides a scientific basis for further research on the hypoglycemic effect of Rhizoma Coptidis-Eupatorium fortunei drug pair.